Narrative in Medicine: Pathways to Healing and Vehicles of Power : Based on the Work of Rita Charon and Amanda Caleb - Song, Fangning (The Journal of Medicine, Humanity and Media, 2026)
This paper adopts Rita Charon’s theory of “narrative medicine” and Amanda Caleb’s critique grounded in Michel Foucault’s concept of “biopower” as a dialogic framework to examine the dual roles of narrative within the medical field. It first analyzes Charon’s approach, which positions narrative competence as a healing bridge that helps close the doctor–patient gap and fosters empathy and human connection. The paper then introduces Caleb’s critical perspective, revealing how narrative also functions as a discourse of power—one that has historically operated through social structures and institutional practices to “medicalize” social problems and legitimize various forms of inequality. The argument advanced here is that Charon’s constructive methodology and Caleb’s critical examination together illuminate two inseparable dimensions of narrative in medicine: narrative serves not only as an essential pathway to healing in clinical practice but also as a complex vehicle of power. Ultimately, the paper contends that in today’s mediated environment, an integrated narrative lens—one that combines empathic practice with sustained reflection on power—holds significant ethical value for cultivating a more inclusive, reflexive, and equitable medical humanities landscape.